Decoding cultural landscapes: guiding principles for the management of interpretation in cultural world heritage sites - Kamel, Ehab (2011)
Conserving the cultural significance of heritage sites - as the guardians of social unity, place identity, and national pride - plays an essential role in maintaining sustainable social development, as well as preserving the variations identifying cultural groups and enriching the interaction between them. Consequently, and considering the importance of the built environment in communicating, as well as documenting, cultural messages, this research project, started in 2007, develops a set of guiding principles for interpretation management, as a process for conserving cultural World Heritage Sites; by maintaining and communicating their cultural significance through managing newly added architectural, urban, and landscape designs to such heritage sites. This research was mainly conducted to investigate and explain a concern regarding a gap that is increasing between people and the cultural heritage contexts they reside- particularly in Egypt- and to suggest a strategy for professionals to understand such sites from a perspective that reflects the public cognition. Adopting Grounded Theory methodology, the research develops a series of principles, which are intended to guide the process of cultural heritage conservation; through a critical analysis of current heritage conservation practices in World Heritage Sites. The research shows how they [the guiding principles] correspond to the contemporary perception of cultural heritage in literature, for which, a thorough discussion of literature, as well as critical analysis of UNESCO’s heritage conventions and ICOMOS charters are carried out. The research raises, discusses, and answers several key questions concerning heritage conservation, such as: whether UNESCO’s conventions target the right heritage or not; the conflicts appearing between heritage conservation documents (conventions and charters); whether intangible heritage can be communicated through design; and the effect of Western heritage ideology on heritage conservation practices. This is carried out through the use of interpretive discourse analysis of literature and heritage documents, and personal site observations and questionnaire surveys carried out in two main World Heritage Sites: Historic Cairo in Egypt and Liverpool city in the UK. The two case studies contributed to the understanding of the general public’s perception of cultural Heritage Sites, and how such perception is reflected in current heritage conservation practices. The thesis decodes cultural World Heritage Sites into three intersecting levels: the ‘cultural significances’ (or ‘open codes’), which represent different categories under which people perceive historic urban landscapes; the ‘cultural concepts’ (or ‘axial codes’), which are considered as the objectives of heritage conservation practice, and represent the general concepts under which cultural significances influence the heritage interpretation process; and finally, the ‘interpretation strategy tactics’, the UNCAP Strategy (or the ‘selective coding’), which are the five overarching principles guiding the interpretation management process in cultural heritage sites. This strategy, the UNCAP (Understanding people; Narrating the story; Conserving the spirit of place; Architectural engagement; and Preserving the built heritage), developed throughout this research, is intended to help heritage site managers, curators, architects, urban designers, landscape architects, developers, and decision makers to build up a thorough understanding of heritage sites, which should facilitate the establishment of more interpretive management plans for such sites, and enhance the communication of meanings and values of their physical remains, as well as emphasizing the ‘spirit of place’; for achieving socio-cultural sustainability in the development of World Heritage Sites.